Keinginan Bunuh Diri pada Mahasiswa Rantau Tinjauan Kecemasan Akademik dan Kelekatan Orang Tua - Alexandra, Laura; Raharjo, Trubus (Jurnal Simki Pedagogia, 2025)
This study aims to determine the relationship between academic anxiety and parental attachment with suicidal ideation in out-of-town students. This study uses quantitative methods and data collection techniques in the form of a Likert scale. The research sample consisted of 125 out-of-town students who were taken using purposive sampling techniques based on certain criteria. The results of the major hypothesis show a significant relationship between academic anxiety and parental attachment with suicidal ideation with an r value of 0.919 and p of 0.000 (p <0.01), which means that there is a very significant relationship between academic anxiety and parental attachment with suicidal ideation with an effective contribution of 84.4%. The majority of students have high levels of academic anxiety and suicidal ideation. This study emphasizes the need for counseling services to reduce academic anxiety and strengthen family support as an effort to improve the mental health of out-of-town students.